EVALUASI KUALITAS LAYANAN PERPUSTAKAAN UNIVERSITAS ISLAM AS SYAFI’IYAH (UIA) - Iffah Budiningsih (Akademika, 2016)
The purpose of this evaluation study is to know the extent to which the quality of library service – UIA inorder to support the learning process for the students of the UIA's next get what information should be improved inthe manifest ' prima ' library services. The object of this research is a student is a student of Strata program S1 in 6(six) faculty (FE, FAI, PEDAGOGY, FH, FST, FIKES) semester 7 (seven) FY 2015/2016 on The Islamic Syafi'iyahUniversity Jakarta (UIA); the number of samples of 84 students. Library service quality evaluation of variablesmeasured using instruments non test by questionnaire.The Data collected is processed and analyzed using descriptive analysis , i.e., Using a central tendency:size: mean, median, mode and size dispersion: score the minimum, maximum, standard deviation score. Theanalysis of statistical data is done with the help of program Excels and 11.5 version SPSS for windowsThe results of research on the quality evaluation of UIA library services can be explained that the average(mean) library service quality score achieved score 59.67 included in categories of "enough". The value of themedian (middle value) score the quality of library services achieve a score 59.0; This gives a meaning that 50%quality of library services show score above 59.0 or above reasonably and 50% of his show score under 59.0 underenough. The value of the mode of 60.0; this indicates that the in General, students give an assessment of the qualityof library services "enough". The lowest score of the quality of service library of 42.0 and highest score achieved,meaning there were 89.0 students who rated lowest 42.0 or "enough" and there are students who rated highest 89.0or "excellent" ,The conclusions of the research library service quality upon evaluative UIA is: 1). In general the quality oflibrary services UIA rated by students in the categories of ' enough '; 2) Assessment of the students in the categoriesof ' enough ' giving opportunities to management library for working to improve the quality of its services for beinga requirement of ' good '; 3) Managing a library to become ' learning resource centre ' among the students andteachers not only required UIA sufficient funds, but also required the managers ' creative and innovative ' inaccordance with the progress of the IPTEKS.